A modified butterfly optimization algorithm for mechanical design optimization problems - Arora, Sankalap; Singh, Satvir; Yetilmezsoy, Kaan (SPRINGER HEIDELBERG, 2018)
This paper presents a modified butterfly optimization algorithm (MBOA) for solving mechanical design optimization problems. The modification is focused on an additional intensive exploitation phase which provides more chance to solutions to improve itself. The performance of the proposed algorithm is validated on fifteen benchmark test functions and three engineering design problems which have different natures of objective functions, constraints and decision variables. The experimental results are analyzed in comparison with those reported in the literature. The results indicate that the MBOA provides very competitive results in comparison with other existing optimization algorithms.
Keywords: Butterfly optimization algorithm; Intensive exploitation; Benchmark functions; Engineering design problems; REDUNDANCY ALLOCATION PROBLEM; PARTICLE SWARM OPTIMIZATION; ENGINEERING OPTIMIZATION; DIFFERENTIAL EVOLUTION; FIREFLY ALGORITHM; COLONY; INTEGER; PARAMETERS; SYSTEM; Engineering